Kilka słów o cnocie (na podstawie dyskusji publicznych) = A few words on virtue (based on public discussions) - Kaczor, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Public discussions confirm that virtue is an important social value, which we understand as moral skills or attitudes that enable a person to do moral good in social life. It is related to a set of rules and a method of conduct and the corresponding values?based behavior. Virtue is a factor that co-creates society and builds the internal order of society. Although virtue involves principles that are universal and immutable, discussions show that virtue is social. This society creates and shapes the understanding of virtue in accordance with the adopted system of values.
Keywords: cnota; etyka; moralność społeczna; pragmatyka; virtue; ethics; social morality; pragmatics